In vitro bioactivity and corrosion resistance enhancement of Ti-6Al-4V by highly ordered TiO2 nanotube arrays - Sarraf, Masoud; Sukiman, Nazatul Liana; Bushroa, Abdul Razak; Nasiri-Tabrizi, Bahman; Dabbagh, Ali; Abu Kasim, Noor Hayaty; Basirun, Wan Jefrey (Springer, 2019)
In the present study, the structural features, corrosion behavior, and in vitro bioactivity of TiO 2 nanotubular arrays coated on Ti–6Al–4V (Ti64) alloy were investigated. For this reason, Ti64 plates were anodized in an ammonium fluoride electrolyte dissolved in a 90:10 ethylene glycol and water solvent mixture at room temperature under a constant potential of 60 V for 1 h. Subsequently, the anodized specimens were annealed in an argon gas furnace at 500 and 700 °C for 1.5 h with a heating and cooling rate of 5 °C min −1 . From XRD analysis and Raman spectroscopy, a highly crystalline anatase phase with tetragonal symmetry was formed from the thermally induced crystallization at 500 °C. Besides, the Ti 2p 3/2 and Ti 2p 1/2 binding energies showed the presence of the Ti 4+ oxidation state. According to the in vitro bioassay, the modified surface proved its outstanding capability in enhancing the bioactivity, where a thick layer of bone-like apatite was formed on the annealed TiO 2 nanotube surface. In addition, the corrosion measurements indicated that the corrosion protection efficiency increased remarkably and reached 87% after annealing at 500 °C. [Figure not available: see fulltext.]. © 2018, Australian Ceramic Society.